Yield and disease resistance of plantain (Musa spp., AAB group) somaclones in Nigeria - Nwauzoma, A.; Tenkouano, A.; Crouch, J.H.; Pillay, M.; Vuylsteke, D.R.; Kalio, L. (Springer, 2002)
This study examined the potential of somaclonal variation for the improvement of plantain. Approximately 500 somaclones each of ‘Agbagba’ (False Horn plantain) and ‘Bise Egome’ (French plantain) were field evaluated for their agronomic performance and response to the black Sigatoka disease. The micropropagated populations were independently generated from a number of suckers from each accession. Significant differences between micropropagated accessions and crop cycles were observed. Differences between plants derived from suckers of the same accession were also expressed, indicating the chimerical nature of variation in the traits studied. None of the plants of the micropropagated populations from ‘Bise Egome’ exhibited significantly better disease tolerance and agronomic performance than the source accession. However,one somaclonal variant of ‘Agbagba’ (‘AO 2B2-2’) expressed lower susceptibility to the black Sigatoka disease. Compared to ‘Agbagba’, ‘AO 2B2-2’ had a higher bunch weight, more fruits per bunch with higher average weight, greater average length, and greater average girth. These data clearly show that, in contrast to previous reports, it is possible to recover superior somaclonal mutants in Musa.